Green Accounting Analysis Based on Triple Bottom Line Theory for Sustainability Development Goals in Districts Bireuen - Murni; Imam Malik (PT Inovasi Pratama Internasional, 2022)
Phenomenon global warming or global warming has Becomes issue warm in various parts of the world so environment the company has also Becomes center attention. This thing because of the business world is one perpetrator active development through something form organizations that do activity use source power limited for reach goals that have been set. Study this aim for analyze implementation of green accounting based on triple bottom line theory for sustainability development goals in the district Bireuen. This thing conducted because existence phenomenon pollution environment in the form of garbage, flood, pollution air, poverty and unemployment. Method analysis in study this use approach qualitative, researcher collect data via documentation and interviews structured to part finance, CSR, and also part environment in the company manufactures in the district Bireuen 12 samples company . Data analysis performed by qualitative. Research results show that company manufacturing in District Bireuen has Secrete related costs with preservation environment in report finance, however still by conventional so that not yet reflects green accounting.